Biochemistry : the molecular basis of life - McKee, Trudy (Oxford University Press, 2017)
"Biochemistry: The Molecular Basis of Life is an intermediate, one-semester text written for students on degree pathways in Chemistry, Biology and other Health and Life Sciences. Aimed at students with one unit of Organic Chemistry, it focuses on essential biochemical principles that underpin the modern life sciences, and offers a balanced coverage of chemistry and biology"--